APPLICATION OF GRAPH THEORY IN AIR TRANSPORT (Perner's Contacts, 2023)
The paper is focused on the graph theory application into the field of air transportation – what are the possibilities of the graph application usage in the air transportation. It deals with the analysis, observation and then with the solution of the application of graph theory to air transport in the planning and optimization of flight path and air traffic flow.
Keywords: air- ways and routes; air traffic; flight operations; matrices; graph theory optimization; air traffic flow management